Philosophy between Power and Powerlessness: A Homage to Karl Jaspers - Raynova, Yvanka B. (Labyrinth, 2019)
The aim of the following paper is to discuss Jaspers' disappointement of politics and his confession about the powerlessness of the (philosophical) Spirit, expressed at the end of his life. This confession may seem to contradict some of his earlier statements and positions. Yet, by analizing the evolution of his views about the complex relation between philosophy and politics, the autor claims that Jaspers' philosophy is an emblematic illustration of a tension, inherent in contemporary philosophy, namely that between the faith in Reason and the scepticism about its potentialities to achieve a substantial changement of human nature and society.